Menjadi Guru Profesional di Era Digital: Integrasi Teknologi Tanpa Mengabaikan Nilai Etika (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyze teacher professionalism in the digital era by highlighting technological integration skills and the application of educational ethics in learning practices. The research employs a literature review approach by examining various studies related to digital competence, the TPACK and SAMR technology integration models, and principles of digital ethics within the educational context. The findings indicate that although teachers have utilized basic technology to support learning, its integration has not fully reached an innovative stage, and the understanding of digital ethics especially regarding data security and digital space management still requires strengthening. The study also reveals that teacher professionalism in the digital era requires a combination of technological proficiency, digital pedagogical ability, and commitment to educational ethics. This research has limitations as it does not involve field data, thus it does not depict actual conditions in depth. Therefore, future studies are recommended to include direct observations and interviews to obtain a more comprehensive understanding. The results emphasize the need for continuous training, infrastructure support, and ethical digital regulations to foster adaptive, innovative, and integrity-based teacher professionalism in the digital era.